A review and outlook of ratiometric optical thermometer based on thermally coupled levels and non-thermally coupled levels - Wang, Chuanlong; Jin, Yahong; Zhang, Ruiting; Yao, Qing; Hu, Yihua (Journal of alloys and compounds, 2022)
The development of current technology imposes more and more requirements for measurement techniques, where one of the most important is temperature measurement. In recent years, non-contact optical thermometry based on fluorescence intensity ratio (FIR) technique has received tremendous attention in inorganic compounds for its promising applications in the electromagnetic field, micro-temperature field and thermally harsh environments. In this work, the current advancement of optical thermometry is reviewed in detail. Herein, the FIR thermometers are classified into two types: thermally coupled levels (TCLs) and non-TCLs based on the different energy level pairs. We investigate the relationship between the absolute sensitivity Sa and relative sensitivity Sr, temperature T and energy difference ∆E based on the TCLs of lanthanide ions. The most important results obtained in each case are summarized, which indicates that some new strategies can extend the temperature operating range, improve the sensitivity and enhance signal discriminability. It is expected that this review will provide important guidance in exploring novel FIR optical thermometry with excellent properties in the future. •Ratiometric optical thermometers based on thermally coupled levels and non-thermally coupled levels are reviewed.•Some novel thermometry strategies are proposed, which can extend the temperature operating range, improve the sensitivity and enhance signal discriminability.•The most important results obtained in each case are summarized.•There are still some challenges to be overcome for the practical applications.